“It’s Our Voices” Cancer-Related Digital Stories by Alaska’s Community Health Workers - Melany Cueva; Regina Kuhnley; Laura J. Revels; Anne P. Lanier; Mark Digman (Adult Education Research Conference, 2011)
Between May 2009 and October 2010, four week-long cancer education courses were provided for 35 community health workers (CHWs) from throughout Alaska. This project explored how cancer-related, digital stories created by CHWs supported their learning journey and provided a tool to share cancer health messages with people in their communities. Digital storytelling combines storytelling with computer-based technology to bring the power of the media to community members. End-of-course written evaluations and qualitative interviews revealed that combining digital storytelling with cancer education was feasible, culturally relevant, and enhanced participant learning.
Keywords: digital storytelling; Alaska Native; cancer education; adult education; community health workers; cancer communication; health technology